Game-based learning : augmented reality in the teaching of geometric solids - Leitão, Rui (2014)
In teaching, the use of virtual and augmented reality has been on the rise, exploring different means of interaction and student engagement. Based on constructivist pedagogic principles, augmented reality pretends to provide the learner/user with effective access to information through real-time immersive experiences. Game-based learning is one of the approaches that have received growing interest. This paper presents the development of a game in a teaching and learning context, aiming to help students acquire knowledge in the field of geometry. The game was intended to develop the following competences in primary school learners (8-10 years): a better visualization of geometric objects on a plane and in space; understanding of the properties of geometric solids; and familiarization with the vocabulary of geometry. The authors will show that by using the game students have improved around 35% the hits of correct responses to the classification and differentiation between edge, vertex and face in 3D solids.